Phenylethanoid glycoside verbascoside ameliorates podocyte injury of diabetic kidney disease by regulating NR4A1-LKB1-AMPK signaling - Xinyun Chen; Min Shi; Letian Yang; Fan Guo; Yan Liang; Liang Ma; Ping Fu (Acta Materia Medica)
Diabetic kidney disease (DKD) is one of the leading causes of end-stage renal disease. Verbascoside is a ubiquitous phenylethanoid glycoside with potent anti-inflammatory, antioxidant, and hypoglycemic properties. This study determined the renoprotective effect of verbascoside against DKD, as well as the underlying mechanism. After administration of verbascoside for 4 consecutive weeks, the fasting blood glucose level, albumin:creatinine ratio, and podocyte damage in diabetic mice were alleviated, especially at a dose of 150 mg/kg/d. Moreover, the inflammatory response, cell apoptosis, and autophagy were improved in a dose-dependent fashion in the kidneys of diabetic mice and high glucose-stimulated podocytes. Verbascoside reversed the elevated NR4A1 expression and suppressed LKB1 to inhibit AMPKα phosphorylation. Silencing NR4A1 inhibited LKB1 and phospho-AMPKα expression, and relieved the stress response in injured podocytes. Taken together, our results indicated that verbascoside alleviates DKD-associated podocyte injury by regulating NR4A1-LKB1-AMPK signaling.